ANALYSIS OF PERSON-ORGANIZATION FIT AND PERSON-ORGANIZATION MISFIT IN ERNST & YOUNG INDONESIA - Wowor, Kristin (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Person-Organization Fit, commonly described as the resemblance of person’s values and organization values, is one of the crucial factors in determining the success of an organization. Employees who are fit in the organization may enthusiastically engage to their job and will have great performance. On the other hand, Person-Organization misfit is one of the reasons why employees quit their job. Exploratory case study methods were used to analyze both variables in this research. The data were collected by interview. Sample of this research is consisted of 8 employees of Ernst & Young Indonesia. Result indicates that there are 3 factors of Person-Organization fit in Ernst & Young Indonesia. The 3 factors of Person-Organization fit that make employees willing to stay in the company are benefits, co-workers, and time flexibility. This research found 4 factors of Person-Organization misfit that are the mismatch between organization’s value and individual’s value, lack of promotion opportunity, small salary, and imbalance type of given job. Keywords: person-organization fit, person-organization misfit